SOCIAL DAMAGE AND THE NEED FOR THE FIGURE OF THE SOCIAL ACTOR - Hernández Rengifo, Freddy (2023)
“The acts of corruption of public officials in Peru generate damages to supra-individual interests, because the right to ““social welfare““ of the citizens is violated (art. 44 of the Constitution) which the State guarantees, and therefore the obligation to compensate arises (art. 35 of the United Nations Convention Against Corruption), and to determine who would intervene as a legitimate subject would be the anti-corruption public prosecutor, in such a way that the violated interest that only has a diffuse existence and not in the individuality of the persons is guaranteed.“